2020
DOI: 10.1136/jnnp-2019-322030
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the centromedian thalamic nucleus for deep brain stimulation

Abstract: ObjectivesDeep brain stimulation (DBS) of the centromedian thalamic nucleus (CM) is an emerging treatment for multiple brain diseases, including the drug-resistant epilepsy Lennox-Gastaut syndrome (LGS). We aimed to improve neurosurgical targeting of the CM by: (1) developing a structural MRI approach for CM visualisation, (2) identifying the CM’s neurophysiological characteristics using microelectrode recordings (MERs) and (3) mapping connectivity from CM-DBS sites using functional MRI (fMRI).Methods19 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
(103 reference statements)
2
54
0
Order By: Relevance
“…RNS stimulation of the CM has been applied in adult patients for the treatment of drug-resistant regional neocortical epilepsy ( 37 ), generalized epilepsy ( 26 ), Lennox-Gastaut Syndrome ( 10 , 38 ), and drug-resistant focal onset-seizures ( 39 ). Seizure frequency of patients with implanted RNS systems often continues to improve over months to years, which implicates the role of neural plasticity induced by programmable closed-loop stimulation ( 16 , 23 ). Further research is needed to better understand the mechanisms underlying the clinical benefits of RNS CM stimulation for the treatment of CAE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RNS stimulation of the CM has been applied in adult patients for the treatment of drug-resistant regional neocortical epilepsy ( 37 ), generalized epilepsy ( 26 ), Lennox-Gastaut Syndrome ( 10 , 38 ), and drug-resistant focal onset-seizures ( 39 ). Seizure frequency of patients with implanted RNS systems often continues to improve over months to years, which implicates the role of neural plasticity induced by programmable closed-loop stimulation ( 16 , 23 ). Further research is needed to better understand the mechanisms underlying the clinical benefits of RNS CM stimulation for the treatment of CAE.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiologic studies reveal that clinically relevant ictal discharges can be detected in the CM nucleus ( 16 , 26 ). Kokkinos et al ( 26 ), performed direct recording of the CM nucleus via RNS showing 3–5 Hz spike and wave activity consistent with their patient's preoperative EEG pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical MRI image-based analysis must be coupled with a deformable atlas overlay, but even this approach may result in an ill-positioned CM nucleus DBS lead. Currently, no reliable functional mapping approach is available for targeting the CM nucleus, though this issue has become a potential area for research focus [23,31]. Furthermore, it has been recently shown that based on the DBS Registry and Database, there exists a large variability in the active DBS contact location within the CM thalamic region [11].…”
mentioning
confidence: 99%